Securing E-mail Communication Using Hybrid Cryptosystem on Android-based Mobile Devices - Teddy Mantoro; Andri Zakariya (Institute of Advanced Engineering and Science, 2012)
One of the most popular internet services is electronic mail (e-mail). By using mobile devices with internet connection, e-mail can be widely used by anyone to exchange information anywhere and anytime whether public or confidential. Unfortunately, there are some security issues with email communication; e-mail is sent in over open networks and e-mail is stored on potentially insecure mail servers. Moreover, e-mail has no integrity protection so the body can be undectected altered in transit or on the e-mail server. E-mail also has no data origin authentication, so people cannot be sure that the emails they receive are from the e-mail address owner. In order to solve this problem, this study proposes a secure method of e-mail communication on Android-based mobile devices using a hybrid cryptosystem which combines symmetric encryption, asymmetric encryption and hash function. The experimental results show that the proposed method succeeded in meeting those aspects of information security including confidentiality, data integrity, authentication, and non-repudiation. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.874